The Effect of Modifiers on the Strength and Impact Toughness of Carbon Fiber Reinforced Plastics - Laura Mustafa; Marat Ismailov; Indira Tashmukhanbetova; Ilyas Ablakatov; Venera Zhumakanova (Pandawa Institute, 2025)
This study utilized epoxy resin, three types of fabric (carbon fiber, glass fiber, and Kevlar), and two plasticizers – tricresyl phosphate (TCP) and oleic acid (OA) – to enhance the impact toughness of carbon fiber-reinforced plastics (CFRP). The polymer matrix used in the experiments was a hot-cured epoxy compound